The Systematic Assessment of Health Worker Performance : A Framework for Analysis and its Application in Tanzania - Leonard, Kenneth L.; Masatu, Melkiory C.; Herbst, Christopher H.; Lemiere, Christophe (World Bank, Washington, DC, 2016)
This paper introduces a simple framework for understanding the dimensions and determinants of health worker performance based on the idea that there can be three different gaps affecting performance: a knowledge gap, the knowledge-capacity gap and the capacity-performance gap. The paper argues that performance is determined by a combination of competence, capacity and effort, and that any of these elements may lead to poor performance, and applies this framework to the measurement of health worker performance in Tanzania. Whilst discussing and highlighting key findings related to the assessment of health worker performance in Tanzania, the overarching objective of the paper is to offer a systematic way to analyze health worker performance through primary data collection and analysis to benefit researchers and countries beyond Tanzania.